“Being a Parent in Finland” - psycho-educative intervention: development and acceptability of a group programme aimed at increasing trust among migrant parents - Sibbie, Pauliina; Laajasalo, Taina; Peltonen, Kirsi; Skogberg, Natalia; Lämsä, Riikka (Informa UK Limited, 2025)
The existing literature highlights distrust among migrant parents in Nordic countries towards child welfare and other services. However, interventions to enhance parental trust are few in number, and descriptions of their development and feasibility testing in a Nordic context are lacking. This paper describes the development of 'Being a Parent in Finland', a psycho-educative group intervention designed for migrant parents to foster institutional trust. The intervention's content and structure are outlined using the Six Steps for Quality Intervention Development framework (6SQuID). Additionally, the paper presents findings from a small-scale pilot study involving thematic interviews with 16 parents and a pre-post survey with 14 parents to assess programme acceptability. The pilot study indicated high acceptability and perceived benefits among parents, although no changes in institutional trust emerged in the quantitative survey. Implications for future development, practice, and research are discussed.